Multiparticipant Geographics Annotation for Interactive Rendezvous and Cooperative Monitoring. (1st October 2011) - Kamejima, Kohji
Abstract : A new framework is presented for multiparticipant coordination of over-the-horizon maneuvering processes. In this framework, geographical information is decentralizedly augmented via the multitude of annotation processes: landmark localization by map builder, connection generation by planner, and GPS tracking by probe vehicles. By integrating the augmentation process on a common satellite image, the subscriber participants reuse the geographics within specific maneuvering context. Based on graph theoretic representation of the multiparticipant augment process, an interactive geographics annotation system was developed and verified within the context of interactive rendezvous and cooperative monitoring.